Theoretical approaches to the study of fundamental British values (FBV) - McDonnell, Jane Louise (PRISM: Casting New Light on Learning, Theory and Practice, 2021)
This article explores some of the critical instruments available to researchers investigating civic nationalist policy and practice via a review of the theoretical approaches that have been brought to bear on one such instance of national education policy, i.e. ‘fundamental British values’ (FBV) in England. The article offers a review of some key theoretical perspectives that have been applied to the study of FBV before offering some reflection on additional theoretical resources that might extend and compliment the insights that these provide. Specifically, I argue that concepts and interventions from the theoretical literature described as ‘radical democracy’ might be of particular use in complementing and extending some of the analysis of FBV in the existing literature.